Efficiency of thiosulfate use as a chlorine neutralizer for water sterilization in vannamei shrimp hatchery culture systems - Dani Pratama Putra; Akmal Izwar; Anis Nugrahawati (Acta Aquatica: Aquatic Sciences Journal, 2026)
The use of thiosulfate as a chlorine neutralizer in water sterilization for vannamei shrimp hatchery culture is essential for maintaining water quality and minimizing organism stress. Thiosulfate effectively eliminates residual chlorine that may be harmful to cultured shrimp, thereby supporting improved cultivation success. This quantitative combined-method study was conducted at the Aquaculture Wet Laboratory of Universitas Almuslim from August to September 2024. The results showed that salinity in treatments A, B, C, and D was consistently 30‰. The highest pH value was recorded in treatment D replicate 2 (8.16), while the lowest was in treatment A replicate 3 (8.10), with an overall average of 8.12. Water temperature across all treatments ranged from 31 to 32°C. Dissolved oxygen (DO) levels were highest in treatment B replicate 1 (5.44 mg/L) and lowest in treatment A replicate 1 and treatment D replicate 2 (5.20 mg/L). Ammonia concentrations in all treatments and replicates were 0.0 mg/L. The highest chlorine concentration was observed in treatment A replicate 3 (0.10 mg/L), whereas treatments C and D showed 0.00 mg/L across all replicates. Bromine levels were also highest in treatment A replicate 3 (0.18 mg/L), with treatments B, C, and D consistently at 0.00 mg/L. Vibrio density in treatments A, B, and C was 0, while treatment D recorded 2,500 CFU/mL in replicate 1, 2,600 in replicate 2, and 8,000 in replicate 3. Keywords: Efficiency; Hatchery Scale; Thiosulfate, Vaname; Vibrio Sterilization, Water Quality